Computer-Assisted Language Learning : Learners, Teachers and Tools. - Son, Jeong-Bae (Cambridge Scholars Publishing, 2014)
Computer-Assisted Language Learning: Learners, Teachers and Tools is an examination of contemporary issues related to learners, teachers and tools in computer-assisted language learning (CALL) environments. It explores the interrelationship among the three components of CALL and presents the findings of recent work in the field of CALL. As the third volume of the Asia-Pacific Association for Computer-Assisted Language Learning (APACALL) Book Series, this book is a significant contribution to ...